Is Classical Liberalism the Source of Libertarianism? - Juruś, Dariusz (Res Publica. Revista de Historia de las Ideas Políticas, 2016)
In this paper I compare John Locke’s and Murray N. Rothbard’s theories of property. The main aim of that comparison is to show that Locke’s theory of property, which seems to be crucial for contemporary libertarians, cannot be the foundation for the libertarian theory. The corollary is that Locke’s theory, resp. classical liberalism, cannot be – as many, including M. N. Rothbard, the main proponent of libertarianism, claim – the source of libertarianism in a strict sense.